The Effect Of Delivery Speed And Product Conditions On Customer Satisfaction Of Regular Postal Services Pt. Pos Indonesia (Persero) In Bandung City - Hariyanto, Hariyanto (Dinasti International Journal of Digital Business Management, 2023)
This study aims to explore the impact of delivery speed and product condition on customer satisfaction using Regular Postal services from PT Pos Indonesia (Persero) in Bandung City. Data were collected through a survey of 100 regular post customers in the city. Data analysis using probability sampling techniques with the simple random sampling method shows that both delivery speed and product condition have a significant effect on Regular Post customer satisfaction. These findings indicate the importance of improvements in delivery service and product quality to increase customer satisfaction. The managerial implications of this study suggest that PT Pos Indonesia (Persero) should prioritise these aspects to improve customer satisfaction and maintain its position in the logistics market. Theoretically, this research makes an important contribution to the understanding of the factors that influence customer satisfaction in the context of courier services.